2018
DOI: 10.1177/0306624x18758853
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Illicit Drug Use Among Indigenous Peoples in Canada: A Test of Social Support Theory

Abstract: Relying on a national stratified random sample of Indigenous peoples aged 19 years old and above in Canada, this study investigates the correlates of illicit drug use among Indigenous peoples, paying special attention to the association between social support measures and illegal drug use. Results from multivariate logistical regression show that measures of social support, such as residential mobility, strength of ties within communities, and lack of timely counseling, are statistically significant correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Specifically, "socially driven legislation and policies have been created to 'rid the Indian from the child' through the Indian Act, Residential School Act, Child Welfare, land dispossessions and so much more" (Absolon, 2016, p. 46). Moreover, historic and ongoing colonialism has created and sustained systems that restrict Indigenous health and wellness through social exclusion and disconnection from land, community and language (Cao et al, 2018; de Finney, 2014; Henry, 2002;Marshall, 2015;Palmater, 2011;Saloojee, 2005;Wotherspoon & Hansen, 2013). This exclusion has associated impacts on cultural identity and wellbeing, as colonialism and other oppressive forces have worked to subvert Indigenous Knowledge Systems, cultures and cultural practices that are inseparable from effectively and collectively strengthening First Nations Peoples' health, healing and wellness.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, "socially driven legislation and policies have been created to 'rid the Indian from the child' through the Indian Act, Residential School Act, Child Welfare, land dispossessions and so much more" (Absolon, 2016, p. 46). Moreover, historic and ongoing colonialism has created and sustained systems that restrict Indigenous health and wellness through social exclusion and disconnection from land, community and language (Cao et al, 2018; de Finney, 2014; Henry, 2002;Marshall, 2015;Palmater, 2011;Saloojee, 2005;Wotherspoon & Hansen, 2013). This exclusion has associated impacts on cultural identity and wellbeing, as colonialism and other oppressive forces have worked to subvert Indigenous Knowledge Systems, cultures and cultural practices that are inseparable from effectively and collectively strengthening First Nations Peoples' health, healing and wellness.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, studies have shown the importance of social support as a protective factor against psychological distress and other important social and health issues in Inuit communities, such as drug use (Cao et al, 2018 ) and suicide (Kral, 2016 ). In a study conducted with Greenland Inuit (Riva et al, 2014a , 2014b ), the association between overcrowding and poor mental well-being was partly explained through reduced social support, independently of other socio-demographic and economic characteristics.…”
Section: Introductionmentioning
confidence: 93%
“…Social supports create the context in which strong social bonds can emerge because enduring relations based on mutual trust are forged through interaction and the giving of assistance ( Cullen, 1994 ). Social support theory has been tested with the dependent variables such as homicide ( Altheimer, 2008 ; Pratt and Godsey, 2003 ), corruption ( Zhang et al, 2009 ), anomie ( Cao et al, 2010 ; Zhao and Cao, 2010 ), and illegal drug use ( Cao et al, 2018 ). Yet, to the best of our knowledge, it has not been applied to the study of victimization, stalking included.…”
Section: Theoretical Frameworkmentioning
confidence: 99%